CUANTIfICACIÓN DEL POTENCIAL EMPRENDEDOR DE LOS ALUMNOS DE LA fACULTAD DE CIENCIAS ADMINISTRATIVAS DE LA UNIVERSIDAD NACIONAL MAYOR DE SAN MARCOS - Pérez Palacios, Emma Emilia (2013)
One option of personal and professional development of students is to start a business, make it grow, create jobs and contribute to local and national development. But, How developed are the entrepreneurial skills of university students? This experimental investigation attempts to determine the ENTREPRENEURIAL POTENTIAL using deductive, and basic quantitative methodology, with correlational cross-sectional design in a total population of 396 students from Faculty of Administrative Sciences. (Tourism, Management and International Business students from Third, fifth and seventh semester) Using the survey as data collection technique and as the instrument of the Entrepreneur Test this is developed by the Ministry of Labour and Employment Promotion, which has the same scientific rigor validations. In the statistical treatment was used statistical processor IBM-SPSS version 20.01 for assigning scores, tabs, charts and statistical indicators. The results of the investigation determined the following: Initiative and Visionary feature are those of the highest scores in the students of the Faculty of Administrative Sciences, students in the first few semesters show lower scores, this means that they enter in college without expectations regarding entrepreneurship. Finally, the evidence according to the results of the Chi Square test statistic that there is a recurring and consistent behavior regarding the entrepreneurial characteristics in Tourism, Management and International Business students of the faculty of Administrative Sciences of Universidad Mayor de San Marcos, as well as at the initial and advanced academic semesters.